ECtHR Practice of Resolving Disputes on Royalty Taxation for the Use of Copyright Objects - SUKHANOVA, Daria; TSURKANU, Siuzanna; ENNAN, Ruslan; BALATSKA, Olha; STRELBITSKA, Lesia (Journal of Advanced Research in Law and Economics; Vol 10 No 7 (2019): JARLE Volume X Issue 7(45) Winter 2019, 2019)
The European Court of Human Rights is increasingly focusing on the compatibility of tax law and intellectual property law with European standards of human rights and fundamental freedoms in the relationship between tax authorities and taxpayers. To increase the efficiency of the work of the bodies of the State Tax Service of Ukraine, as well as the judicial authorities of Ukraine and to ensure an adequate level of protection of the rights and interests of individuals and legal entities, it is important to analyze the ECtHR's practice of resolving royalties for the use of copyright objects. The research methodology consists of general theoretical and special scientific methods, namely: dialectical, historical, systemic, modeling and abstraction, induction, deduction, analysis, synthesis, comparative-legal method, and theoretical modeling. The study analyzes the ECtHR's practice of the settlement of disputes on royalty taxation for the use of copyright objects, clarifies the grounds and key positions of the European Court of Human Rights for resolving disputes related to royalty taxation, and reveals the value of the case-law of the European Court of Human Rights in the development of the tax system of Ukraine.